2021
DOI: 10.1016/j.scitotenv.2020.142203
|View full text |Cite
|
Sign up to set email alerts
|

Levels of human Rotaviruses and Noroviruses GII in urban rivers running through the city mirror their infection prevalence in populations

Abstract: Enteric viruses exposed to water pose a huge threat to global public health and can lead to waterborne disease outbreaks. A sudden increase in enteric viruses in some water matrices also underpins the prevalence of corresponding waterborne diseases in communities over the same time period. However, few efforts have been focused on water matrices whose viral pollution may best reflect the clinical prevalence in communities. Here, a one-year surveillance of human enteric viruses including Enteroviruses (EnVs), R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Virus particles should thus be considered as complementary measures to bacterial indicators, once the potential role of water in transmission of viruses and the outcomes should not be excluded. In addition, recent studies demonstrated the presence of several types of enteric viruses in water matrices, such as Rotaviruses A (RVA), Noroviruses (NoVs), Hepatoviruses (HVA) and Adenoviruses (HAdVs) [10,[37][38][39][40][41][42][43]. Some authors note that HAdVs can be used as virological indicators of human contamination and, consequently, a marker for water quality.…”
Section: Discussionmentioning
confidence: 99%
“…Virus particles should thus be considered as complementary measures to bacterial indicators, once the potential role of water in transmission of viruses and the outcomes should not be excluded. In addition, recent studies demonstrated the presence of several types of enteric viruses in water matrices, such as Rotaviruses A (RVA), Noroviruses (NoVs), Hepatoviruses (HVA) and Adenoviruses (HAdVs) [10,[37][38][39][40][41][42][43]. Some authors note that HAdVs can be used as virological indicators of human contamination and, consequently, a marker for water quality.…”
Section: Discussionmentioning
confidence: 99%
“…NoVs are the most common pathogenic cause of global outbreaks of acute gastroenteritis, with common symptoms, such as vomiting, diarrhea and stomach cramps [5,6]. NoVs are mainly transmitted via the fecal-oral route and have a high incidence in autumn and winter [7,8]. Human NoVs (HuNoVs) include GI, GII and GIV, with GII being the most common [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no correlation between bacterial contamination and the presence of enteric viruses (Qiu et al 2015). Viruses of fecal origin, such as Rotavirus (RVA) and Norovirus (NoVs), can be isolated from surface water sources, and several studies have already shown that their presence can compromise the quality of drinking water (fongaro et al 2015;Shi et al 2021).…”
Section: Introductionmentioning
confidence: 99%